PARVIMONAS MICRA AND FUSOBACTERIUM NUCLEATUM SEPTIC ARTHRITIS: A RARE ANAEROBIC DOUBLE TROUBLE - Shenoy, Padmaja Ananth; Gupta, Rohit; Vishwanath, Shashidhar; Naik, Monappa A; Shetty, Seema; Chawla, Kiran (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Septic arthritis is a condition initiated by pathogenic inoculation of joints either by direct or hematogenous route, necessitating immediate medical attention. Among aerobic bacteria, Staphylococcus aureus and Streptococcus spp. are commonly found in association with septic joints. Anaerobes are very rarely involved in the causation of septic arthritis with an estimated rate of <1%. We are presenting a case of septic arthritis of knee joint by Parvimonas micra and Fusobacterium nucleatum, both being constituents of microbial flora in the oral cavity and gastrointestinal tract. Gram stain and anaerobic culture incorporated along with the aerobic culture of synovial fluid have played an important role in the preliminary diagnosis of anaerobic septic arthritis in this case.